Investigation of strategies to decrease food waste in college and university foodservice - Whitehair, Kelly J. (Kansas State University, 2011)
This study used two operational research components to explore strategies to decrease waste in university dining facilities. Component one assessed students’ beliefs and behaviors toward food waste in a selected dining center. The relationships between students’ food waste behavior, sustainability beliefs, and demographics were evaluated with the use of a self-administered survey and continual food waste monitoring. This study also assessed whether simple prompt-type message interventions had an impact or if the addition of more personally relevant feedback-based data elicited a greater change in consumer beliefs and behaviors On average, more than 57 grams of edible food was left on each tray. Food waste behaviors were not influenced by demographic factors. Individuals with higher levels of food waste beliefs also disposed of less edible food items. The simple prompt-type messages stimulated a 15% reduction in food waste. The addition of more personalized feedback-based messages did not stimulate a change above that of the prompt message. These findings indicate that simply making university students aware of the topic of food waste may be useful in improving their behaviors. Component two evaluated the operational feasibility of implementing tray free dining at Kansas State University Dining Services. Telephone interviews with managers of university dining facilities involved in tray free dining were conducted to identify best practices. Focus groups of students were used with a written survey to gain insight into their perceptions of tray free dining. Benefits included: decreased waste, reduced chemical, resource, and food costs, and improved student satisfaction. Managers identified complaints and dining room cleanliness as negative outcomes. Student involvement, education, and communication were strongly recommended by both managers and students. This research supports the recommendation to consider the implementation of tray free dining at Van Zile. Decreased costs, improved satisfaction, and positive public perception are likely positive outcomes.
Keywords: Food waste; Tray waste; Tray free dining; University foodservice; Sustainability; Messaging; Management (0454); Sustainability (0640)